2006
DOI: 10.1037/0012-1649.42.5.913
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of externalizing behavior problems for boys and girls across preschool: The roles of emotion regulation and inattention.

Abstract: Although externalizing behavior typically peaks in toddlerhood and decreases by school entry, some children do not show this normative decline. A sample of 383 boys and girls was assessed at ages 2, 4, and 5 for externalizing behavior and at age 2 on measures of emotion regulation and inattention. A longitudinal latent profile analysis was performed and resulted in 4 longitudinal profiles of externalizing behavior for each gender. Poor emotion regulation and inattention were important predictors of membership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
231
3
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(251 citation statements)
references
References 81 publications
(119 reference statements)
9
231
3
8
Order By: Relevance
“…Initial analyses found that parents of younger children endorsed behavioral items as being more frequent than parents of older children. This finding is consistent with longitudinal research which found a peak of behavior problems around age two that declines by age four and five (Hill, Degan, Calkins, & Keane, 2006). From a developmental perspective, younger children may be more prone to externalizing behaviors, in part, because their ability to communicate displeasure through other means is limited (i.e., speech).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Initial analyses found that parents of younger children endorsed behavioral items as being more frequent than parents of older children. This finding is consistent with longitudinal research which found a peak of behavior problems around age two that declines by age four and five (Hill, Degan, Calkins, & Keane, 2006). From a developmental perspective, younger children may be more prone to externalizing behaviors, in part, because their ability to communicate displeasure through other means is limited (i.e., speech).…”
Section: Discussionsupporting
confidence: 81%
“…Although the option of creating separate cut scores by gender was considered, it was ultimately decided against doing so because of the absence of a gender effect for the clinical sample, the small effect size observed in the non-clinical sample, and previous research that suggests that externalizing profiles in preschoolers do not substantially vary across gender. Longitudinal research has found that the trajectory for externalizing behaviors for males and females are similar in preschool aged children (Beyer, Postert, Muller, Furniss, 2012;Hill, Degan, Calkins, and Keane, 2006). For example, Hill, Degan, Calkins, and Keane (2006) found that although reasons for membership in externalizing groups were different across genders, the trend in the developmental course across genders for preschool aged children was markedly similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing recognition of the relevance of emotion regulation to developmental psychopathology (Gross & Thompson, 2007). Compared to broader emotion regulation research (Aldao et al, 2010;Hill et al, 2006) the study of emotion regulation in individuals with intellectual disabilities is at an early stage (McClure et al, 2009). However, recent studies have begun to investigate the relationship between emotional dysregulation, problem behaviours and psychiatric disorders (Sappok et al, 2014) and our findings further highlight the link between emotional dysregulation and problem behaviours.…”
Section: Discussionmentioning
confidence: 99%